Lidar observations of ice-nucleating particle (INPC) and ice crystal number (ICNC) concentrations: height-resolved INPC-ICNC closure studies in mixed-phase altocumulus layers - Ansmann, Albert; Buhl, Johannes; Mamouri, Rodanthi-Elisavet; Engelmann, Ronny; Seifert, Patric; Nisantzi, Argyro; Hadjimitsis, Diofantos G.; Sciare, Jean (My University, 2017)
During the six-week Cyprus-2015 field campaign in March and April 2015, conducted in the framework of the BACCHUS project (Impact of Biogenic versus Anthropogenic emissions on Clouds and Climate: towards a Holistic UnderStanding, collaborative project of the seventh EU framework programme, ENV. 2013.6. 1-2), we observed the evolution of extended liquid-water altocumulus fields with subsequent heterogeneous ice formation. The altocumulus layers developed in aged Saharan dust layers between 3.5 km (-20 C) and 7.5 km height (-35 C cloud top temperature). We observed such altocumulus developments on 12 days. By applying our recently developed polarization-lidar method we estimated the ice-nucleating particle concentration (INPC, immersion freezing) at cloud level (before the clouds developed and after their dissolution). Simultaneously performed Doppler lidar observations of the terminal …
Keywords: Ice-nucleating particle concentrations (INPC); Ice crystal number concentrations (ICNC)